P0371DENTAL CARIES INDUCED BY CNM-POSITIVE STREPTOCOCCUS MUTANS DERIVED FROM IGA NEPHROPATHY PATIETNS IN RATS INDUCED GLOPERULONEPHRITIS LIKE IGA NEPHROPATHY. (6th June 2020) - Nagasawa, Yasuyuki; Naka, Shuhei; Wato, Kaoruko; Nomura, Ryota; Misaki, Taro; Ito, Seigo; Kida, Aritoshi; Nanami, Yoshimasa; Hasuike, Yukiko; Takahiro, Kuragano; Matsumoto-Nakano, Michiyo; Nakano, Kazuhiko
Abstract: Background and Aims: IgA nephropathy (IgAN) is one of most common primary glomerulonephritis, whose pathogenesis had remained unclear. We had reported that Cnm- (+) Streptococcus mutans, a kinds of major dental caries bacteria. Cnm- (+) S. mutans had strong collagen binding ability, resulting in high pathogenicity. We reported that the prevalence of Cnm- (+) S. mutans in IgA nephropathy is significantly higher than that in control (Misaki-T et al, Clin Exp Nephrol 2015; 19:844-50), and that Cnm- (+) S. mutans in IgA nephropathy was associated with proteinuria (Misaki-T et al, Sci Rep 2016 ). We also reported C.rectus and S. mutans increased proteinuria synergistically (Misaki-T et al, Nephron, 2018). In this point, there is no direct evidence that Cnm- (+) S. mutans could induce IgA nephropathy. In this study, we evaluated the renal lesions in rats which had dental caries induced by Cnm- (+) S. mutans derived from IgA nephropathy patient to confirm the pathogenesis of IgA nephropathy like lesions induced by Cnm- (+) S mutans. Method: Cmn-(+) S. mutans from saliva of IgA nephropathy patients was orally administrated into 4 weeks old male Sprague-Dawley rats. Addition of sugar to water had been kept during study period to develop dental carits. At week 34 after the infection, blood, urine, and kidney samples were evaluated. Kidney samples were stained by Periodic Acid-Schiff (PAS), IgA, C3. Historical evaluation by electron microscope analysis was also performed. Results: At week 34, plaque score and dental caries score in infectious rats significantly elevated, compared with control rats (P<0.001) (Figure 1). These findings suggested Cmn-(+) S. mutans from IgA nephropathy patients induced dental caries in rats. PAS staining revealed the significant mesangial proliferation. At week 34, the prevalence of IgA deposition in infections rats was higher than that in control rats (52.4% vs 4%), and the prevalence of C3 deposition in infectious rats was also higher than that in control rats (42% vs 11%) (Figure 2). Incidence of hematuria was also significantly higher in dental caries group than control. Electron microscopy analysis revealed high dense deposit in mesangial areas. Conclusion: Cmn-(+) S. mutans from saliva of IgA nephropathy patients could induce IgA-dominant infection-associated glomerulonephritis, or IgA nephropathy.